2022
DOI: 10.3389/fgene.2022.1002928
|View full text |Cite
|
Sign up to set email alerts
|

Causal association between inflammatory bowel disease and IgA nephropathy: A bidirectional two-sample Mendelian randomization study

Abstract: Background: An association between inflammatory bowel disease (IBD) [which includes ulcerative colitis (UC) and Crohn’s disease (CD)] and IgA nephropathy (IgAN) has been discovered in observational studies, but the causal relationship is still unknown. The aim of this study was to clarify the causal link between IBD (which includes UC and CD) and IgAN via a two-sample Mendelian randomization (MR) analysis.Methods: Eligible single-nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Although the association between IgAN and IBD may be coincidental, emerging evidence suggests a potential common underlying mechanism in disease pathogenesis. 21 , 22 Recent studies have identified risk loci in genes involved in intestinal mucosal integrity, and common risk alleles for both IgAN and IBD. 23 , 24 The gut-kidney axis hypothesis supports a key role for imbalances between immunity and microbiota in the development or exacerbation of IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between IgAN and IBD may be coincidental, emerging evidence suggests a potential common underlying mechanism in disease pathogenesis. 21 , 22 Recent studies have identified risk loci in genes involved in intestinal mucosal integrity, and common risk alleles for both IgAN and IBD. 23 , 24 The gut-kidney axis hypothesis supports a key role for imbalances between immunity and microbiota in the development or exacerbation of IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors effectively reduce the production of inflammatory mediators and the recruitment of inflammatory cells, thereby controlling inflammation driven by overactive Th17 cells. Despite increasing research indicating that IL-17 and Th17 cells play a central role in IgAN and other immune-mediated glomerular diseases, particularly through mechanisms related to the gut microbiome environment [82,193,194], the inhibition of IL-17 A has not consistently produced positive outcomes in some conditions, such as Crohn's disease and IgAN treatment. Moreover, its effectiveness has shown limitations in certain renal disease models [195][196][197].…”
Section: Il-17 Inhibitormentioning
confidence: 99%
“…Interestingly, a genome-wide association showed that most IgAN loci are directly associated with inflammatory bowel disease, suggesting that IgAN pathogenesis is likely linked to the intestine 16 . Similarly, a Mendelian randomized study indicated causality between inflammatory bowel disease and the development of IgAN 17 . Th17 expression in the gut is induced by intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%